Body Mass Index: An Analysis Study on Football Athletes - Didi Yudha Pranata (Universitas Negeri Semarang, 2023)
This study aims to analyze the characteristics of the body mass index of soccer athletes. This study uses a qualitative descriptive research method. Sampling in this study used a total sampling technique so that the entire population was taken as a sample of 20 people. The instrument used for data collection uses the Body Mass Index (BMI) instrument. Benchmark Reference Assessment (PAP) based on Body Mass Index (BMI) criteria became the basis for analyzing the data and then analyzing it with the help of Ms. Excel. The results showed that the body mass index (BMI) of Football Academy talent football athletes showed an average score of Normal BMI, but there were two athletes who were in BMI with the criteria of being overweight 5%, the total percentage of BMI obesity was 10%, normal BMI was 50% , and 35% lean BMI. The conclusion from this study is that the athletes at Talenta Football Academy have problems with their body mass index, this is because 50% of the athletes have an abnormal body mass index classification, this is feared to hinder Talenta Football Academy's overall performance. The researcher advises the management of Talenta Football Academy to be able to pay attention to the nutritional status of each athlete and to be able to make food programs for athletes and to evaluate their nutritional status every month by measuring their body mass index.